Integrating Discussion Technique in Project-Based Learning for Vocational School Student - Zayyin Az Zahro; Muhlisin Rasuki; Widya Oktarini (Universitas Islam Negeri Palopo, 2025)
In the context of a suburban school setting characterized by low motivation and poor engagement, this study seeks to examine the potential of integrating the Discussion Technique and Project-Based Learning (PjBL) to enhance vocational high school students’ comprehension of procedural text. The study was conducted over a period of six meetings, utilizing a Classroom Action Research (CAR) design. The data was gathered using a variety of methods, including semi-structured interviews with four students, field notes, pre-test and post-test findings, and classroom observations. The findings indicate that the integrated approach enhances students’ ability to recognize the linguistic elements and structure of procedure texts, generate more cohesive written outputs, and engage more fully in group-based learning activities. As demonstrated by the descriptive comparisons between the pre-test and post-test results, students exhibited enhanced step sequencing, more suitable use of imperative verbs, and improved structure in their procedure text composition. The observation data revealed positive behavioral changes, including a reduction in passive participation in classroom activities and an increase in discussion participation and project work. The validity of these findings was further supported by interview data, which demonstrated that structured conversations led to improvements in students’ confidence in sharing ideas, a reduction in confusion, and enhanced subject comprehension as the students approached the assignment completion stage. The present study indicates that enhancing English learning results in vocational school environments, as well as effective pedagogical scaffolding for low-motivation vocational learners. Keywords: Discussion Technique; Project-Based Learning; Procedure Text; Vocational School